Α-Keto tetrahydrofuran lignan glucosides from the Bangladeshi medicinal plant Terminalia citrina inhibit estradiol (E2) induced proliferation in cancer cells. (January 2018) - Muhit, Md. Abdul; Umehara, Kaoru; Noguchi, Hiroshi
Abstract: EtOAc extract from the leaves of Terminalia citrina collected in Bangladesh were separated, and seven previously undescribed α-keto tetrahydrofuran lignan glucosides (terminalosides Q to W) were isolated and characterized. NOESY analysis of 1 H NMR spectra and ECD spectroscopic data analysis revealed the absolute stereochemistry of the tetrahydrofuran ring of the isolated constituents as being a (7 S, 8 R, 8′ S )- configuration in terminalosides Q to U and a (7 R, 8 R, 8′ S )- configuration in terminalosides V and W. All of the isolated compounds were evaluated for their estrogenic and anti-estrogenic properties using two types of estrogen-responsive human breast cancer cell lines (MCF-7 and T47D). Terminaloside R, which has a dioxymethylene group in its aromatic ring, inhibited 90% of estradiol-enhanced cell proliferation in T47D and MCF-7 cells at concentrations of 0.01 μM and 0.1 μM, respectively. On the other hand, terminaloside T, the analogous compound which has two oxymethyl groups in place of dioxymethylene, suppressed 90% of cell proliferation selectively in T47D cells at a concentration of 0.01 μM. However, terminaloside W, the 7 R -stereoisomer of terminaloside R, only showed moderate activity. Graphical abstract: Terminaloside R, an anti-estrogenic α-keto furo lignan glucoside isolated from Bangladeshi medicinal plant Terminalia citrina . Image 1 Highlights: Seven unknown α-keto tetrahydrofuran lignan glucosides were isolated. Absolute stereochemistry in furan ring of constituents were also characterized. Cotton effects in their ECD spectra were practical methods for the characterization. Terminalosides R and T inhibited estradiol-enhanced breast cancer cell proliferation.